Handbook of research on Web 20 and second language learning [ - Thomas, Michael , 1969- (Hershey, PA : Information Science Reference, 2009)
"This book investigates how those involved in education can respond to the opportunities offered by the Web 2.0 technology"--Provided by publisher.
Description based on print version record
Includes bibliographical references (p 546-596) and index
Keywords: Internet in education; Language and languages -- Computer-assisted instruction; Second language acquisition -- Computer-assisted instruction